Morphological and nociceptive effects of mechanical vibration on the sciatic nerve of oophorectomized Wistar rats - Camila Mayumi Martin Kakihata; Ana Luiza Peretti; Maria Luiza Serradourada Wutzke; Alana Ludemila de Freitas Tavares; Lucinéia de Fátima Chasko Ribeiro; Rose Meire Costa Brancalhão; Gladson Ricardo Flor Bertolini (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aim: To evaluate the effects of whole-body vibration in the sciatic nerve of oophorectomized Wistar rats, on nociceptive and morphological parameters, such as fiber, axon, and myelin sheath diameters, G ratio, number of nerve fiber and nuclei of Schwann cells, and percentage of connective tissue. Method: Sixty-four rats were used in the groups sham-operate and oophorectomy (n = 32/group); after surgical procedures, each group was subdivided into four: euthanized in the 12th week, untreated and treated for four weeks; and euthanized in the 16th week, untreated and treated for eight weeks. The treatment with vibration was performed with a 60 Hz frequencies, for 10 minutes, three days a week, with duration of 4 or 8 weeks. Nociception was evaluated later, in the right paw, by means of a digital analgesimeter, prior to surgery, at the beginning and at the end of the protocol. After the trial period, the sciatic nerve was dissected for examination of the general morphology of the tissue and morphometric analysis; later, the animals were euthanized. Results: Regarding nociception and the morphometry of the sciatic nerve, independent of oophorectomy and treatment time, there was no statistically significant difference within and between groups. Also, the general morphology of the tissue in all groups had characteristics that were preserved. Conclusion: The mechanical vibration did not alter the nociceptive threshold and the morphological aspects of nerve fibers in oophorectomized Wistar rats.